Neural network signal interpretation for optimization of chromatographic protein purifications - Klein, Eric J.; Rivera, Sheyla L. (Zielona Góra: Uniwersytet Zielonogórski)
Mobile phase pH and salt gradient steepness are optimized for the separation of protein mixtures using gradient elution ion-exchange chromatography. The optimization method utilizes a factorial experimental design to generate an experimental matrix. The resulting chromatographic peaks are classified into six distinct classes based on peak geometry by a vector quantizing neural network (VQN).
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka